Pengaruh Kedalaman Ulir Terhadap Kekuatan Tarik Benda Pada Produk Threaded Bush Secara Aktual - Rachenja Harunni Nelvis; Ihsan Saputra; Nurul Ulfah (Jurnal Teknologi dan Riset Terapan (JATRA), 2022)
One of the tests that are often carried out in the industrial world is the tensile test. Tensile test is the methods used to test and determine the strength of material by applying a load/force to the product used and placed on an axis in the opposite direction. This test uses a threaded bush product, which has an outer diameter of 6,94 mm, a length of 44 mm, using a M5 × 0.8 tap using 316 L Stainless Steel material. The product has a difference size in the depth of the thread length produced by the CNC machine, this is due to the instability of the machine used, resulting in varying thread lengths. The length of the thread is, with average minimum of 8,40 mm and maximum ranging from 14,40 to 18,40 mm. The purpose of this research is to determine the (Tensile Strength) and the resulting maximum load. In this test, two groups were used, the control group and the experimental group. The product without thread as the control group, and the product with variations in depth as the experimental group. From the tests carried out, the results showed that the product without thread had the highest load and tensile strength, 1,570 kg and 0.4153 kN/mm2. While in the experimental group, the product sizes 8.40 and 14.40 had the maximum load and the highest tensile strength of 1,558 kg and 0.4121 kN/mm2. While the product sizes 18.40 and 14.40 have the lowest load and tensile strength, 1,538 kg and 0.4067 kN/mm2.